Researching Everyday Childhoods Time, Technology and Documentation in a Digital Age - Thomson, Rachel (Bloomsbury Academic, 2018)
This book is open access and available on www.bloomsburycollections.com. It is funded by the University of Sussex, UK. How can we know about children's everyday lives in a digitally saturated world? What is it like to grow up in and through new media? What happens between the ages of 7 and 15 and does it make sense to think of maturation as mediated? These questions are explored in this innovative book, which synthesizes empirical documentation of children's everyday lives with discussions of key theoretical and methodological concepts to provide a unique guide to researching childhood and youth. Researching Everyday Childhoods begins by asking what recent 'post-empirical' and 'post-digital' frameworks can offer researchers of children and young people's lives, particularly in researching and theorising how the digital remakes childhood and youth. The key ideas of time, technology and documentation are then introduced and are woven throughout the book's chapters. Research-led, the book is informed by two state of the art empirical studies - 'Face 2 Face' and 'Curating Childhoods' - and links to a dynamic multimedia archive generated by the studies.